CAREER MOTIVATIONS (CAREER INSIGHT, CAREER IDENTITY, AND CAREER RESILIENCE) BASED ON AREA OF INTERESTS OF NUTRITION STUDENTS - Iput Tintin Lathifah; Ika Ratna Palupi; Siti Helmyati (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Nutrition-related career exists in various work sectors, from health care and education to food manufacture and business. No studies have been conducted on career motivations of nutrition students in three main areas of nutrition field. This study aimed to identify career motivations (career insight, career identity, and career resistance) in nutrition students of Universitas Gadjah Mada (UGM) with an interest in either of three nutrition main areas, i.e. clinical nutrition, community nutrition, or foodservice management. Methods: This study used a quantitative method and involved 75 college students of nutrition major in UGM. Variables in this study were nutrition students’ interest toward nutrition main areas and career motivations which consisted of career insight, career identity, and career resilience. Data collection used a validated questionnaire. Data analysis was performed using descriptive and analytical statistics. Results: Subjects with an interest in clinical nutrition, community nutrition, or foodservice management had career insight in medium category with almost equal proportions (i.e. 73.9%, 71.9% and 75%, respectively), career identity in medium category (73.9%, 53.1% and 70%, respectively) and career resilience in high category (60.9%, 56.3% and 50%, respectively).Conclusion: Career insight levels of UGM nutrition students are relatively equal in each area of interest in the nutrition field. Students with a clinical nutrition interest have the highest career resilience while students with a community nutrition interest have the highest career identity. Future studies need to employ a qualitative technique to better understand factors underlying students’ motivation in choosing area of interests in nutrition field.